British Association of Dermatologists guidelines for the management of people with cutaneous squamous cell carcinoma 2020. (18th January 2021) - Keohane, S.G.; Botting, J.; Budny, P.G.; Dolan, O.M.; Fife, K.; Harwood, C.A.; Mallipeddi, R.; Marsden, J.R.; Motley, R.J.; Newlands, C.; Proby, C.; Rembielak, A.; et al.
Abstract : Plain language summary available online